On testimony, Fiction and Postmemory as Promises of Redemption. Three Texts in the Centenary of the Tragic Week (Palimpsesto, 2020)
In January 1919 took place the violent events that would be known under the name of “Tragic Week” (considered by some scholars as the first antisemitic pogrom in Latin America). These events have been the object of analysis from different points of view and have also generated many speculations about memory and oblivion of society in general and in the Jewish community in particular.This paper considers three texts that approach the subject with a dynamic that interweaves testimony, memory and fiction, through a variety of complex resources. In other words, we do not seek to analyze works that merely thematize the “Tragic Week”, but those that put personal memories in scene and that move over the narrow (and often slippery) border between memory, identity and fiction. The study starts from Koshmar (Nightmare) by Pinie Wald (originally published in Yiddish, in 1929). This text is an unavoidable reference on the matter and has been presented by some critics as an antecedent of Argentine non-fiction (it was reissued in 2019, on the occasion of the centenary of the events narrated). Then will consider more recently produced works, that recover those facts trough the porosities between the remembered, the inherited and the imagined: El arresto (2001) by Perla Suez and María Domecq (2007) by Juan Forn.
Keywords: tragic week; koshmar; anti-semitism; memories; self-fiction